HIV-1 capsid interactions with Nuclear Pore Complex components support nuclear entry via affinity gradient - Ivo Melčák; Ryan L. Slack; Zachary C. Lorson; Andres Emanuelli Castaner; Krisztina Ambrus; Jonathan S. Winkjer; Karen A. Kirby; Robert A. Dick; Stefan G. Sarafianos (Proceedings of the National Academy of Sciences, 2026)
Before entering the nucleus, the HIV capsid core [composed of capsid (CA) proteins] must translocate through the Nuclear Pore Complex (NPC). This process relies on direct interactions between CA and the phenylalanine-glycine (FG) repeats in nucleoporins (NUPs) within the NPC. FG repeats are generally classified into three canonical motifs: FG, GLFG, and FxFG, which are differentially distributed along the NPC axis: FG and FxFG motifs are predominantly at the cytoplasmic periphery and in the nuclear basket, whereas GLFG motifs are primarily in the central channel of the NPC. We demonstrate that the capsid engages the diverse FG repeats with markedly different affinities. Notably, GLFGs of NUP98 located in the central channel display significantly increased affinity to CA than conventional FGs/FxFGs. NUP153, which is located at the nuclear basket, contains an atypical FxFG that is adjacent to a PSGV sequence, thus forming additional favorable interactions. We designate this nonconventional FxFG motif as an “FG super-motif.” In addition, the C-terminus of NUP153 also contains a cluster of basic residues that serve as an enhancer of the NUP153 FG super-motif, dramatically increasing CA affinity by ~1,000-fold. Other binding enhancers for FG motifs were also identified in NUP58 and POM121 that are in the central channel and its nuclear boundary, respectively. Affinities of NUP58, POM121, and NUP153 enhancers to CA increase with proximity to the nuclear basket. Thus, we propose that the diverse FG repeats and their binding enhancers create an affinity gradient that potentiates HIV capsid translocation through the NPC.